BIBLIOMETRIC ANALYSIS ON NUMERICAL LITHOFACIES IDENTIFICATION FOR RESERVOIR CHARACTERIZATION IN THE PERIOD OF 1980 -2021 - Muhamad Apriniyadi; Rosmalia Dita Nugraheni; Cahyaningratri Prima Riyandhani; Cahaya Rosyidan Rosyidan; Yarra Sutadiwiria; Imam Setiaji Ronoatmojo (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2022)
The term "electrofacies" was introduced in 1980 by Serra and Abbott, it had been developed promptly since 2009. The development was triggered predominantly by wireline logging technology and artificial intelligence technology. The electrofacies categorization was intended to facilitate the study of reservoir characterization. However, it is difficult to formulate deterministically, due to the uniqueness of the depositional environment and geological processes that involve many physical properties. At least, there are 369 articles which were obtained from Scopus sources in the period of 1980 - 2021. In this bibliometric analysis, we regrouped the articles into four groups, i.e. “pattern recognition” “facies analysis”, “objectives” and “quality”. This grouping was attained on the methods of co-occurences, co-authorship, citation analysis and bibliographic coupling using VOSviewer software. The distance and coupling between themes will determine the level of quality and quantity of discussion between them. The quality of the objective resides in the certainty value of the lithology controlled by transportation or diagenetic events. For example, sand and shale which are siliciclastic lithology will have a higher degree of certainty than carbonate rocks. Therefore, the wide gap occurred during the application of artificial intelligence, especially for complex facies and uncertain geological conditions. The application of artificial intelligence is not solely functional without involving geological analysis. The implication is some researchs are still needed from this point of view, so the electrofacies role cannot be independent without developing models of the diagenetic process.